مدى معرفة المرأة بمعلومات البطاقة الارشادیة المرفقة بالملابس والمفروشات في مدینة بغداد (Journal of the College of Education for Women, 2019)
It takes a long time and a lot of money to choose and provide clothes. It is soothingnecessary to care of them in order to use it another time. There is no Disposable clothesuntil now, like other things in the house which we used for once then we dropped, then wecan use new one without any time or effort can be mentioned like needles, nappy, tissuesand etc.The clothes are different; people should take care of and clean them again in order touse them again. The right care of clothes would make them last for a long time. So, there isno need to buy a new one instead of them in a short time. This thing provides time andeffort for the people and the family, to affect positively on the family’s budget.We should use to care for the clothes by following the right and suitable means,because there are many clothes have very easy ways to deal with them successfully athome in order to look elegance and acceptable. This is something very important to thosewho are specialists at home economics directly towards the family.For inferring the extent of women's knowledge of the instructional label informationthat comes with the clothes and furniture in Baghdad, the researcher has performed a test(a subjective one) consisting of ( 30 ) items and distributed them to ( 4 ) axis's whichinvolve primary information that every woman should learn. The test has been applied on (100 ) responders and proved that such knowledge is of a low level especially in a plainsymbolic axis. Eventually, the researcher has presented some suggestions andrecommendations.